Measuring food insecurity: the frequency and severity of coping strategies - Maxwell, Daniel G. (International Food Policy Research Institute, 1995)
Defining and interpreting food security, and measuring it in reliable, valid and cost-effective ways, have proven to be stubborn problems facing researchers and programs intended to monitor food security risks. This paper briefly reviews the conceptual and methodological literature on food insecurity measurement, describes a particular method for distinguishing and measuring short-term food insecurity at the household level, and discusses ways of generalizing the method. The method developed enumerates the frequency and severity of strategies relied on by urban households when faced with a short-term insufficiency of food. This method goes beyond more commonly-used measures of caloric consumption to incorporate vulnerability elements of food insecurity as well as the deliberate actions of household decisionmakers when faced with food insufficiency.